Increased risk of head injury in pediatric patients with attention deficit hyperactivity disorder. Issue 4 (21st July 2019) - Grigorian, Areg; Nahmias, Jeffry; Dolich, Matthew; Barrios, Cristobal; Schubl, Sebastian D.; Sheehan, Brian; Lekawa, Michael
Abstract: Objective: The prevalence of attention deficit hyperactivity disorder (ADHD) in the general pediatric population is 7%, whereas the prevalence in trauma is unknown. We hypothesized pediatric patients with ADHD would have a higher risk of involvement in a mechanism of injury (MOI) requiring constant attention to surroundings, such as a bicycle collision. Methods: The Pediatric Trauma Quality Improvement Program (2014–2016) was queried for patients with ADHD. Patients, less than 16 years of age, with ADHD were compared to those without ADHD. Results: The prevalence of ADHD was 2.5% (2, 866). ADHD patients had higher risk for bicycle collision (odds ratio [OR], 1.85; 95% confidence interval [CI], 1.59–2.15; p  < .001). ADHD bicyclists were less likely to wear a helmet (9.4% vs. 18.2%, p  = .003) and had a higher rate of traumatic brain injury (TBI; 55.6% vs. 39.7%, p  < .001), compared to non‐ADHD bicyclists. Conclusions: Pediatric ADHD patients have a 60% higher risk of being involved in a bicycle collision. ADHD patients that are involved in a bicycle collision are less likely to wear a helmet with a higher rate of TBI. Increased public awareness, education, and supervision may help reduce risk of bicycle collisions and TBI in this population.